Perbandingan Efektivitas Promosi Agrowisata dengan Menggunakan Media Sosial dan Media Konvensional di Kabupaten Banyuwangi (Jurnal Komunikasi Pembangunan, 2019)
The increasing number of social media users in Indonesia certainly provides a great opportunity to optimize social media as a communication medium. One of them is social media used as a promotional media for agricultural development, on the other hand it is not only social media that is used for media promotion. In fact, in the field many found that conventional media / traditional media are still used as promotional media. The research focused on the effectiveness of agro-tourism promotion media using social media and conventional media in Banyuwangi Regency. The research approach uses quantitative data with survey methods and uses questionnaires as a data collection tool. The sample of this study were three agro-tourism groups from three sub-districts in Banyuwangi Regency with the total number of social media users being 226 visitors and 146 visitors for conventional media users. Data were collected in May-July 2018. Data were analyzed by SPSS 22 and Mann Whitney Test descriptively. The results showed that Pvalue Svarna Agrotourism was 0.226, this value is greater than the significant value (α = 0.05) which indicates that conventional social media and media are different. Pvalue of Pb Agro Tourism is 0.003, this value is smaller than the significant value (α = 0.05) which indicates that sociald media and conventional media have no difference. While the value of Values of Steam Agro Tourism is 0.443, this value is greater than the significant value (α = 0.05) which indicates that conventional social media and media are different.